Urban Metabolism and the UM-US-SC Nexus (Asian Journal of Social Science Studies, 2019)
This paper discusses the current increasing trend of urbanization and environmental implications of urbanizations, potential solutions for the problems caused by overpopulation & urbanization. Global challenges like rapid population growth, resource scarcity, climate change, biodiversity loss are the centres of environmental management issues as well. As cities are recognized as the key to resolve these global environmental issues and sustainability are the main focuses of this century’s development, this paper identifies the sustainability of cities or urban sustainability (US) as the fundamental principal or core idea underlying possible pathways to solve those major challenges with an emphasis on urban metabolism (UM) (Section 2~6). The literature review covers the evolution and development of UM concept, metaphors of UM perspective, definitions of UM, its applications, challenges and future directions. Six types of UM methodologies are discussed as well. This paper demonstrates that UM is a promising approach for building US and connects it to the concept of smart cities (SC). Relating contents like the differences and connections between smart cities and sustainable cities, the politics of data, opportunities & challenges of SC are presented in Section 7. The last part of this paper proposes a Nexus among UM, US and SC; which reveals both of the apparent and underlying correlations & interactions among these three concepts and their practices.